Utilization of Twitter as an Educational Tool to Improve Reading Literacy in Indonesian Language Students - Pratika, Sendy Dien; Jaja, Jaja; Rosmaya, Elin (Devotion : Journal of Research and Community Service, 2024)
Digital power and lack of access to relevant literature. Twitter, as one of the most popular applications in the era of digital culture, can be used as an educational tool to increase the reading literacy of Indonesian language study program students. The integration of Twitter in the learning of Indonesian language study program students can facilitate access to information, increase creativity, develop reading literacy skills, expand social networks, and encourage student participation. The library research method is used to analyze secondary data from published research articles. The research question raised was, "How can the use of Twitter as an educational tool increase reading literacy among Indonesian language study program students in the era of digital culture?" The findings show that the integration of social media, especially through Twitter, can make a positive contribution to Indonesian language learning by utilizing its features to facilitate access to information, increase creativity, develop reading literacy skills, expand social networks, and encourage student participation. Overall, the use of Twitter in Indonesian language learning promises to significantly increase student reading literacy while building engagement, motivation and a strong learning community.